2021
DOI: 10.3389/fmicb.2021.761997
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation Is Crucial for Efficient Copper Bioleaching From Bornite Under Mesophilic Conditions: Unveiling the Lifestyle and Catalytic Role of Sulfur-Oxidizing Bacteria

Abstract: Biofilm formation within the process of bioleaching of copper sulfides is a relevant aspect of iron- and sulfur-oxidizing acidophilic microorganisms as it represents their lifestyle in the actual heap/dump mining industry. Here, we used biofilm flow cell chambers to establish laminar regimes and compare them with turbulent conditions to evaluate biofilm formation and mineralogic dynamics through QEMSCAN and SEM-EDS during bioleaching of primary copper sulfide minerals at 30°C. We found that laminar regimes tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Mounting evidence supports the notion that the efficient bacterial sulfur oxidation activities in the leaching process require the development of a complex and orchestrated biofilm matrix. This involves either native or externally introduced acidophiles colonizing the ore surface ( Bobadilla-Fazzini, 2014 ; Dong et al, 2020 ; Bobadilla-Fazzini and Poblete-Castro, 2021 ), or relates to the aggregation degree of planktonic cells prior to biofilm formation ( Bellenberg et al, 2015 ; Melaugh et al, 2016 ; Yavari et al, 2019 ). Consequently, it is less likely that the improved desulfurization process can be solely attributed to the activity of sulfur-oxidation bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence supports the notion that the efficient bacterial sulfur oxidation activities in the leaching process require the development of a complex and orchestrated biofilm matrix. This involves either native or externally introduced acidophiles colonizing the ore surface ( Bobadilla-Fazzini, 2014 ; Dong et al, 2020 ; Bobadilla-Fazzini and Poblete-Castro, 2021 ), or relates to the aggregation degree of planktonic cells prior to biofilm formation ( Bellenberg et al, 2015 ; Melaugh et al, 2016 ; Yavari et al, 2019 ). Consequently, it is less likely that the improved desulfurization process can be solely attributed to the activity of sulfur-oxidation bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore suggested that the putative Cu-metabolizing microorganisms isolated might not be good candidates for bioleaching applications. Nevertheless, because of the well-known advantages of using microbial consortia for bioleaching (Brune and Bayer, 2012;Liu et al, 2020;Bobadilla-Fazzini and Poblete-Castro, 2021), microorganisms from this study could still have potential applications, particularly due to their cold-tolerance or in other systems with lower Cu-concentrations.…”
Section: New Metal(loid)-tolerance Insights Into Known Environmental ...mentioning
confidence: 99%